Production and quality evaluation of banana wine using Saccharomyces cerevisiae - Entonu, E E; Boluwatife, O V; Ngene, AC; Egbere, O J (Bangladesh Journal of Scientific and Industrial Research, 2025)
This study was carried out to investigate yeast dynamics, explore the impact of physicochemical conditions on yeast, identify microorganisms during fermentation, and assess overall quality in banana wine production. Results showcased intriguing trends. Yeast cell counts surged to 2.52x106 cfu/ml at 144 hours, following a 48–120-hour plateau. Total aerobic count decreased as fermentation progressed from 5.6x102 to 2.0x102 in the treated sample, and similar decreases were observed in the other samples. Alcohol content varied, with Sample of known yeast strain at 10.5%, highlighting the influence of yeast strains and fermentation conditions. pH values consistently decreased. Temperature fluctuations (25°C to 24.5°C) indicated dynamic fermentation conditions. Titratable acidity increased (0.98g/100ml to 1.48g/100ml), impacting sensory attributes, and specific gravity declined (1.090 to 1.040). Microbial composition unveiled Saccharomyces cerevisiae, Bacillus sp, Lactobacillus sp, and Penicillium sp. Sensory evaluation results indicated significant acceptability in terms of aroma, texture, taste, color, and overall acceptability, with the sample containing a pure and known yeast strain being the most preferred by the panelists. These findings emphasize the importance of aligning sensory characteristics with the choice of yeast strain. In summary, this research advances the understanding of banana wine production and quality assessment, with implications for the beverage industry's ongoing growth. Bangladesh J. Sci. Ind. Res. 60(1), 25-34, 2025